A Syntactical Analysis on Sentence Structure used in Two Adelesâ€™s Songs - Purnomoadjie, Wiyogo; Mulyadi, Mulyadi (PANYONARA: Journal of English Education, 2019)
Syntax is the branch of linguistics that described the sentence structure, songs are composed by a collection of phrases and sentences are also interested to be studied through syntax. This research aims to describe the sentence structure through a tree diagram and to find the sentence structure appears in two Adeleâ€™s song, especially in writing a descriptive text. This research employs a descriptive qualitative method. Two kinds of data collection were used to collect the data, those are observation and documentation. In observation, the researcher did something such as listening to the songs â€œSomeone Like Youâ€ and â€œDonâ€™t You Rememberâ€ and listening to the songs again focusing on the lyrics. In the documentation, analyzing the lyrics from each song and writing down all the lyrics of two songs to be analyzed use tree diagram. Having analyzed the data, then, finally found sixty forms of the structure of the two Adeleâ€™s songs. From the two of Adeleâ€™s songs used as the samples in this thesis, grammatical sentence mostly appears rather than an ungrammatical sentence. Through the discussion, the researcher also found the substandard English words, such as Ainâ€™t, youâ€™d, Iâ€™ll, youâ€™re, didnâ€™t, couldnâ€™t, isnâ€™t.